Optimising Inventory Management Strategies for Cost Reduction in Supply Chains: A Systematic Review - Olaniyi, Oluwadamilare Abiodun; Pugal , Paul Sundar (Universitas Medan Area, 2024)
This systematic review investigates and synthesises the complexities of optimising inventory management strategies for cost reduction in supply chains. The research utilised a systematic review methodology to comprehensively analyse inventory management strategies for cost reduction in supply chains, employing key search terms across databases such as PubMed, Scopus, and IEEE Xplore. A total of 50 journals were initially identified, followed by a rigorous screening process based on pre-defined criteria, including 23 relevant published articles written in English. Examining global supply chain dynamics and sector-specific challenges in local inventory management, the review proposes three key strategies: Just-in-Time (JIT) and lean inventory practices, advanced analytics and predictive modelling, and collaborative supply chain partnerships. Drawing on empirical evidence and sector-specific examples, the review demonstrates the effectiveness of these strategies in mitigating costs and enhancing overall supply chain efficiency. The policy implications underscore aligning business practices with proposed strategies, offering policymakers insights for formulating guidelines and incentives. Contributions to knowledge include a comprehensive framework for businesses to navigate contemporary supply chain challenges. At the same time, suggestions for further studies advocate for deeper explorations into emerging technologies and regional variations to refine and expand inventory management strategies.